Vagus Nerve Stimulation as a Potential Therapy in Early Alzheimer’s Disease: A Review - Vargas-Caballero, Mariana; Warming, Hannah; Walker, Robert; Holmes, Clive; Cruickshank, Garth; Patel, Bipin (Frontiers in Human Neuroscience, 2022)
Cognitive dysfunction in Alzheimer’s disease (AD) is caused by disturbances in neuronal circuits of the brain underpinned by synapse loss, neuronal dysfunction and neuronal death. Amyloid beta and tau protein cause these pathological changes and enhance neuroinflammation, which in turn modifies disease progression and severity. Vagal nerve stimulation (VNS), via activation of the locus coeruleus (LC), results in the release of catecholamines in the hippocampus and neocortex, which can enhance synaptic plasticity and reduce inflammatory signalling. VNS has shown promise to enhance cognitive ability in animal models. Research in rodents has shown that VNS can have positive effects on basal synaptic plasticity and synaptic function, tune inflammatory signalling, and limit the accumulation of amyloid plaques. Research in humans with invasive and non invasive VNS devices has shown promise for the modulation of cognition. However, the direct stimulation of the vagus nerve afforded with the invasive procedure carries surgical risks. In contrast, non-invasive VNS has the potential to be a broadly available therapy to manage cognitive symptoms in early AD, however the magnitude and specificity of its effects remains to be elucidated. Ongoing clinical trials with healthy individuals and patients with early AD will provide valuable information to clarify the potential benefits of non-invasive VNS in cognition and AD. Whether invasive or non invasive VNS can produce a significant improvement on memory function and whether its effects can modify the progression of AD will require further investigation.